A Diaminodiacid (DADA) Strategy for the Development of Disulfide Surrogate Peptides. Issue 18 (11th August 2020) - Qi, Yun‐Kun; Qu, Qian; Bierer, Donald; Liu, Lei
Abstract: Disulfide bond‐containing peptides are useful molecular scaffolds with diagnostic and therapeutic applications due to their good biological activity and good target selectivity, but their utility is sometimes limited by the lability of the disulfide moiety under reducing conditions and in the presence of disulfide bond isomerase. The development of disulfide surrogates with improved redox stability has been an area of ongoing research; and one possible strategy is based on a diaminodiacid (DADA) moiety, which can be used to synthesize the disulfide bond replacement peptides with precise structures and enhanced stability through automated solid‐phase peptide synthesis (SPPS). This review summarizes recent developments in the DADA‐based SPPS of peptide disulfide surrogates. Some representative applications and structural studies on the DADA‐based disulfide surrogates are described. Abstract : Disulfide‐containing peptides represent promising molecular scaffolds for diagnostic and therapeutic applications. This review summarizes the recent advances in diaminodiacid‐based solid‐phase synthesis of disulfide surrogate peptides.